(3MGTjI TQM BOGH GdHMKs - (3GdcGTj Ch GdcGTGfj, jMji Hf CMeO, J HYO (B745 (3g`s ((3MSGes)
(3ChdgG (B:s
(3HSe Gddg (B... ((3bhdg GdefI (B) (3hGdXGgQ Gfg CQGO bhdg GdefI Cj GdhGgH GdYbd hef bGd GdefI jgOe GdUfjYI YfO TQMg ade (B... ((3YdjfG Sdc (B) (3cCfg bjd de de jHOC GdeUfa HMeO Gddg JYGdi CLGH Hbhdg Sdc ef (B...s
(3BNQgG (B:s
... (3bhdg ef GdJQOjO GdePchQ aXgQ Gf GdLhGH Yf GeJKGd gPG GdefY djS EdG WQjb GdJQOjO hGKHGJ Gfg ZjQ eVQ ceG SHb aj eKGd GdefY GdZjQ GdeVeQ aj GdJfHjg GdSGHb ajOQGc (B.s
(3JHUQI GdYfhGf (B:s
(3TQM GdTQhGfj Ydi BOGH eMeO Hf CTQa GdSeQbfOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\135s
(3cTa GdXfhf (B1\39s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs